2022
DOI: 10.3390/math10111853
|View full text |Cite
|
Sign up to set email alerts
|

Effective Identification and Localization of Single and Multiple Breathing Cracks in Beams under Gaussian Excitation Using Time-Domain Analysis

Abstract: The output response of any intact oscillatory system subjected to a Gaussian excitation is also Gaussian in nature. On the contrary, when the system contains any type of underlying nonlinearity, the output signal is definitely non-Gaussian. In beam structures, the presence of fatigue-breathing cracks significantly influences the dynamic response characteristics under Gaussian excitation. The presence of such cracks alters the response to be nonlinear, and the non-Gaussianity of the system will arise. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Integration of optical flow and information entropy was used by Xin et al [21] and similar advanced algorithms have been reported. Similar high-end algorithms have been reported for the prognosis of stationary structures like structural beams by Al-hababi et al [22], and Kumar and Singh [23].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Integration of optical flow and information entropy was used by Xin et al [21] and similar advanced algorithms have been reported. Similar high-end algorithms have been reported for the prognosis of stationary structures like structural beams by Al-hababi et al [22], and Kumar and Singh [23].…”
Section: Introductionsupporting
confidence: 77%
“…The frequency domain response, η i is derived from the full spectrum of η(t) and the time domain response η(t) may be attained from the time integration of equation (22).…”
Section: Time and Frequency Responsesmentioning
confidence: 99%
“…Therefore, the development of a generalized procedure for the localization of multiple breathing cracks is challenging. [13][14][15][16][17][18][19][20][21][22][23][24][25] Nonlinear multiple breathing cracks detection utilizing direct zeros estimation of higher-order frequency response function was studied by Chomelette. 19 However, the method is less accurate in localizing the crack close to the support (cantilever beam).…”
Section: Introductionmentioning
confidence: 99%
“…There exists a lot of research evidence on extraction of low amplitude nonlinear features such as superharmonics and mixed harmonics or intermodulations from the vibration response using frequency domain approaches. [1][2][3][4][5][6][7][8] Only very few studies are completely time-domain approaches [22][23][24][25] and they mostly aim at addressing single breathing crack identification. The extraction and enhancement of the nonlinear features in the time domain especially toward multiple breathing crack localization is highly complex and challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation